Assessing the impact of research capstone preparation in the economics curriculum. Issue 3 (12th September 2020) - St. Clair, Priscilla Cooke; Hunnicutt, Lynn; Travis, Karen
Abstract: It is challenging for economics major programs to support an undergraduate research capstone where the goal is for all majors to complete a research project that creates new knowledge. Our program has found a way to achieve this for all of our majors in the face of resource constraints and varying student skill levels, and has done this without requiring econometrics or a research methods class or sacrificing quality. Our method includes having assignments that require students to use peer-reviewed economics journal articles in most upper-level economic elective courses. We describe our method and "capstone prep" assignment variants, and, using regression analysis on a data set of undergraduate economics majors from 2007 through 2018, find that particular assignments appear to significantly improve capstone outcomes.